Republic of Croatia : Third Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2006)
The report provides the third Review of the Republic of Croatia Under the Stand-By Arrangement (SBA). Policies under the SBA have sought to reduce Croatia's savings-investment imbalance and stabilize the external debt-to-GDP ratio. Executive Directors agreed that the main success of the program has been a fundamental improvement of Croatia's public finances. Executive Directors emphasized the need for fiscal actions to mitigate domestic demand pressures, tightening of prudential regulations to safeguard financial stability in the face of accelerating credit growth, and steps to restore the momentum of privatization.